A model reducing researchers' challenges in projects: build trust first for better mental health - Alex Zarifis; Xusen Cheng (Cogent Business & Management, 2024)
Despite the many benefits for researchers that participate in a project there are several challenges that create a cumulative, negative, effect on their mental health. Existing research focuses on four stages of a project: Forming, Storming, Norming and Adjourning. This research adds a fifth stage, Post-Project Collaboration, as this stage is implicitly or explicitly a part of most research projects. For example, a post-doctoral researcher expects to be credited for their work even if it is published after the end of the project. The specific challenges for each of the five stages are identified. This enables the leader to focus on a manageable number of challenges at each stage. Trust should be built during the first stage to cover four specific topics: Trust in the leader, process, evaluation method and trust in being credited in published work. Conflict does not emerge as a challenge at the initial stages but later.
Keywords: 650; Projects; research teams; leadership; trust; mental health